Role performance of Village Panchayat in the field of Agricultural Development and Village welfare in Unnao District of Uttar Pradesh - Ritesh Dube , O. P. Yadav , Sheelesh Kumar ,; Amit Kumar Singh (Indian Journal of Extension Education, 2016)
The project intended to study the role performance of Village Panchayants with respect to role in the field of Agricultural Production and Social welfare of village community the histogram of specific role performed by the Village Panchayats showed the frequency of responses perceived by the respondents.It was analysed that the maximum (93.75%) respondents opined in favour of motivation farmers for availing financial and technical help by the local cooperatives (87.50%) by making efforts for the availability of chemical fertilizers, pesticides etc. (83.75%) of technology transfer for the maintenance of livestock and making efforts for improving cattel breeds (78.75%) of assisting for assured supply of irrigation by canal and public tube-well (75.00%) or preparation of agricultural production plan (75.00%) by arrangement for reviving the traditional village cottage industries (68.75%) by making efforts for undertaking user reclamation (62.50%) of distribution of land among landlesses, (62.50%) of organising fair and meals and (56.25%) to organise and layout field demonstration. It was also analysed the social services and maintenance of buildings, provision of drinking water facilities. It was calculated that respondents opined in favour of the perception that the agricultural sub-committee was responsible for pooling and making available agricultural resources to the cultivators. It was studied the social welfare committee was worked for constructing Village Panchayats buildings, culverts, irrigation channels, wells and tanks, improvement of family welfare programme, contagious diseases and epidemic and eradication of social evils like gambling, untouchability etc.